Fatty acid profile and lipid oxidation of Longissimus thoracis and biceps femoris muscles in goats - Ismail, Madihah (2015)
A scientific research on the relationship between obesity and their related diseases and diet has been emerged. One of the factors is overconsumption of the red meats such as pork and beef. In addition to the fat content of muscle and adipose depots, the fatty acid composition of lipids affects meat quality. Furthermore, relevant reports are difficult to use for comparisons, in that samples were collected from muscles and fat depots at various anatomical locations and experiments entailed different objectives, designs and methodologies. The general purpose of this study was to identify the fatty acid composition and oxidative stability within 7 days postmortem in Longissimus thoracis and Biceps femoris muscles in goats. In this study, a total of 8 Boer goats of 4-5 months old, having body weight of 30.54±0.47 kg were sourced from a commercial goat farm. After evisceration and dressing, the carcasses were split in two. The Longissimus thoracis and Biceps femoris muscles were taken from one side of the carcasses. The samples were divided into two parts, one for lipid oxidation and another one for fatty acid analysis. Samples for fatty acid analysis were snap frozen in liquid nitrogen and kept at -80ºC while lipid oxidation samples were placed in the refrigerator (4ºC) and the oxidative stability monitored for 0, 1, 4 and 7 day post-mortem. The major differences in fatty acid composition between the two muscles were that proportion of C18:2n-6 and C20:5n-3 was significantly higher in BF compared with LT. The proportion of C14:0 and C14:1 was numerically higher in LT muscle than the BF. Contrarily, the proportion of C20:4n-6 tended (p=0.07) to be higher in BF muscle compared with LT. There was no significant difference between the muscles in the proportion of major fatty acids such as C16:0, C18:0 and C18:1n-9. However, the proportion of C18:1n-9 and CLA cis-12 trans-10 was numerically higher in LT than BF. The total n-6 fatty acids was significantly (p<0.05) higher in the BF than LT. The lipid stability of both muscles was shown in The TBARS values. The TBARS value of LT and BF did not differ on 0, 1, 4 and 7 day post-mortem. Regardless of muscle, TBARS value increased as post-mortem storage progressed. The TBARS value on day 0 and 1 was not significantly different but was different from those observed on days 4 and 7.